Ritual Kirtan dan Pengalaman Spiritual Umat Sikh di Gurdwara Ciputat, Tangerang Selatan - Rizka Aulia; Siti Nadroh (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2026)
Kirtan is one of the main forms of worship in the Sikh religion, carried out through the chanting of shabad (holy words) originating from Sri Guru Granth Sahib Ji accompanied by music. For Sikhs, Kirtan is not only part of a religious ritual, but also serves as a means to get closer to Waheguru, deepen spiritual experience, and strengthen togetherness within the community. This study aims to examine the implementation of the Kirtan ritual and uncover the spiritual meaning felt by the congregation at Gurdwara Ciputat, South Tangerang. This study uses a qualitative method with a phenomenological and anthropological approach. Data were obtained through participatory observation, in-depth interviews with religious leaders and Sikh congregations, and literature studies related to the research theme. Data analysis was carried out using Clifford Geertz's symbolic theory to understand the symbolic meaning contained in the practice of Kirtan. The results show that Kirtan has five main spiritual meanings, namely as a medium for conveying emotions, a means of spiritual communication with God, a vehicle for aesthetic appreciation, a source of inner peace, and a form of preservation of Sikh traditions and culture. Viewed from Edmund Husserl's phenomenological perspective, the spiritual experience born through the practice of Kirtan is understood as a process of religious appreciation that fosters self-awareness, ego control, and closeness to Waheguru. Furthermore, Kirtan also contributes to the cultivation of discipline, simplicity, and the internalization of spiritual teachings in the daily lives of Sikhs.